Research funding and academic engagement : a Singapore case - Hooi, Rosalie (2020)
Universities have been called upon to work more closely with the industry and actively take part in economic development. Research funding has been used as an instrument to direct research agenda and promote technology partnership. The study examines how research funding is associated with various academic engagement in the context of Singapore, a country with explicit policies to encourage university-industry collaboration. Based on a survey with 276 academics in STEM fields, we find that research funding does play a role in academic engagement. In particular, funding from industry is observed to have a significant correlation with patent licensing, consultancy, and serving on advisory board. In addition to funding, more on-the-ground university and government effort to support academic scientists in their commercialisation activity, in particular, new ventures, would be helpful.